Bloomington, Osborne County - Mick, Nathan (Kansas State University, The Chapman Center for Rural Studies, 2012)
The town of Bloomington, Kansas, started out as Tilden in 1870 and received its name change three years later. At its peak, around 1930, Bloomington had seventy-five residents and boasted a bank, grocery store, telephone company, restaurant, lumberyard, stockyards, and two churches.
Nathan Mick, “Bloomington, Osborne County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/135.
Keywords: Agriculture; Bloomington; Great Depression; Osborne County; Tilden; Kansas